2007
DOI: 10.1021/ja077383m
|View full text |Cite
|
Sign up to set email alerts
|

Size Limitations for the Formation of Ordered Striped Nanoparticles

Abstract: A combination of immiscible molecules in the ligand shell of a gold nanoparticle (NP) has been shown to phase separate into a rippled structure; this phase separation can be used to direct the assembly of the NPs into chains. Here we demonstrate that only NPs within a certain size range can form chains, and we conclude that the rippled morphology of the ligand shell also exists only within that given size range. We corroborate this result with simulations of the ligand arrangement on NPs of various sizes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
97
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(103 citation statements)
references
References 19 publications
(52 reference statements)
6
97
0
Order By: Relevance
“…However, recent work indicated that surface structure does not significantly affect the proposenity for small AuNPs to fuse with single component bilayers 25 , and furthermore small AuNPs exhibit similar structural characteristics in water independent of morphology 44 . Experimental evidence also suggests that for small AuNPs, the two ligand species fully separate to form Janus particles 49 . However, the expected electrostatic attraction between the MUS end groups and the bilayer would cause the MUS ligands in the Janus morphology to approach the surface in the same orientation as for an all-MUS particle 20 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent work indicated that surface structure does not significantly affect the proposenity for small AuNPs to fuse with single component bilayers 25 , and furthermore small AuNPs exhibit similar structural characteristics in water independent of morphology 44 . Experimental evidence also suggests that for small AuNPs, the two ligand species fully separate to form Janus particles 49 . However, the expected electrostatic attraction between the MUS end groups and the bilayer would cause the MUS ligands in the Janus morphology to approach the surface in the same orientation as for an all-MUS particle 20 .…”
Section: Resultsmentioning
confidence: 99%
“…We used polydisperse AuNPs with a mean gold core size of 5-6 nm coated with a 2:1 MUS:OT monolayer [24][25][26][27] as an intermediate composition between the all-MUS and 1:1 MUS:OT compositions studied in simulations. These AuNPs were large enough to not form Janus morphologies 49 but sufficiently small that insertion would be expected 25,32 . Details of particle characterization are in the Supplementary Methods.…”
Section: Resultsmentioning
confidence: 99%
“…[ 209 ] where mobility enabled by the particle curvature allows mixed monolayers of immiscible molecules to segregate into nm-scale stripes. [ 210 ] While electro-hydrodynamic co-jetting is limited to production of cylindrical and spherical particles due to surface tension effects, more complex shapes can be produced using microfl uidic strategies. One such technique, called stop fl ow lithography (SFL), enables remarkable control over particle anisotropy and was fi rst demonstrated by Doyle and colleagues.…”
Section: Fabrication and Assembly Of Anisotropic Particlesmentioning
confidence: 99%
“…Glotzer theoretically demonstrated that a length mismatch between two dislike thiolates is sufficient to drive the formation of stripe like domains on the surface of gold nanoparticles of diameters in the range 2.5-8.0 nm [32]. For smaller particles the formation of the so-called Janus particles is favored, with the two dislike ligands segregated on two hemispherical surfaces.…”
Section: Monolayer Structurementioning
confidence: 99%